Diffuse Myocardial Inflammation in COVID-19 Associated Myocarditis Detected by Multiparametric Cardiac Magnetic Resonance Imaging. (May 2020) - Luetkens, Julian Alexander; Isaak, Alexander; Zimmer, Sebastian; Nattermann, Jacob; Sprinkart, Alois Martin; Boesecke, Christoph; Rieke, Gereon Jonas; Zachoval, Christian; Heine, Annkristin; Velten, Markus; Duerr, Georg Daniel
Abstract : Supplemental Digital Content is available in the text.